O estudo da usinagem em torneamento da superliga à base de níquel Pyromet 31v - Burian, Elton Carlos [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The search for materials with higher properties and characteristics (wear resistance, oxidation, corrosion, etc.) has driven research of various materials. Among the materials that are being studied with such properties and characteristics are super alloys based on nickel which has an important role in the aeronautical, automotive, marine, production of gas turbines and now in space vehicles, rocket engineering , experimental aircraft, nuclear reactors, steam-powered plants, petrochemical and many other applications because besides having all the characteristics and properties mentioned above also have an excellent performance at high temperatures. The super alloy based on nickel studied in this work is the super alloy Pyromet 31v normally used in the manufacture of exhaust valves in common engines and diesel engines of high power by cater requirements such as mechanical strength and corrosion resistance at temperatures of approximately 815 ° C. The objective of this work is to produce results to demonstrate more specific information about the real influence of coatings on cutting tools and cutting fluids in turning and thus promote the optimization of the machining of these alloys. The super alloy Pyromet 31v was processed through turning, being performed with various machining parameters such as cutting speed, feed rate, depth in conditions of Minimum Amount of Fluid (MAF), abundant fluid, cutting tools with coating and without coating in early in his work life and with wear. After turning were obtained several samples of chips and the part generated during the machining process, was measured roughness of the material, subsequently made macrostructural analysis of the tools used order to detect possible wear and microstructural analysis of samples collected being that the latter was used for Optical Microscopy, Scanning Electron Microscopy (SEM) and ... (Complete abstract click electronic access below)

A busca por materiais com propriedades e características (resistência ao desgaste, a oxidação, a corrosão, etc.) mais elevadas tem impulsionado pesquisas de vários materiais. Dentre os materiais que estão sendo pesquisados com tais propriedades e características estão as super ligas à base de níquel que tem um papel importante nas indústrias aeronáutica, automobilística, marinha, na produção de turbinas a gás e agora também em veículos espaciais, na engenharia de foguetes, aviões experimentais, reatores nucleares, plantas movidas a vapor, indústrias petroquímicas e muitas outras aplicações, pois além de possuírem as características e propriedades já mencionadas também possuem um excelente desempenho à alta s temperaturas. A super liga à base de níquel estudada neste trabalho é a super liga Pyromet 31v normalmente utilizada na confecção de válvulas de exaustão em motores comuns e a diesel de alta potência por atender a requisitos como resistência mecânica e à corrosão em temperaturas de aproximadamente 815°C. O objetivo deste trabalho é gerar resultados para demonstrar informações mais específicas a respeito da real influência de recobrimentos, em ferramentas de corte, e dos fluidos de corte, no torneamento e assim promover a otimização da usinagem destas ligas. A super liga Pyromet 31v utilizada passou por torneamento, sendo este realizado com diversos parâmetros de usinagem como velocidades de corte, avanço, profundidade, em condições de Mínima Quantidade de Fluido (MQF), Fluido abundante, ferramentas de corte com recobrimento e sem recobrimento no início de sua vida de trabalho e com desgaste. Após o torneamento foram obtidas várias amostras de cavacos e da peça gerados durante o processo de usinagem, foi medida a rugosidade do material, posteriormente ... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Usinagem; Ligas de niquel; Resistencia de materiais; Materiais - Fadiga; Machining; Cutting Tools; Characterization